GREEN GROWTH VERSUS RESOURCE-BASED GROWTH: DEVELOPMENT TRADE-OFFS IN EAST KALIMANTAN UNDER INDONESIA'S LOW-CARBON TRANSITION - Rustam, Rustam; Jafri, Mastur; Aulia, Meilani (Penelitian dan Pengembangan Ilmu, 2025)
East Kalimantan faces a critical development paradox as Indonesia pursues low-carbon transition goals while maintaining economic dependence on resource extraction. This study examines the tension between green growth imperatives and resource-based development strategies in East Kalimantan, Indonesia's coal mining and palm oil production hub. Employing qualitative methodology through document analysis, policy review, and secondary data synthesis, this research investigates how provincial development trajectories navigate competing priorities of environmental sustainability and economic growth. Findings reveal fundamental trade-offs manifesting in policy inconsistencies, investment patterns favoring extractive industries despite renewable energy commitments, and socioeconomic vulnerabilities for resource-dependent communities. Empirical evidence demonstrates that coal production reached 695 million tons in 2023, contradicting national carbon neutrality targets for 2060. The study contributes theoretical insights into resource curse dynamics within transition economies and practical implications for development policy in resource-rich regions undergoing decarbonization pressures.